Information on Financing the Construction of Warsaw University Library - Rzesos, Robert (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The University of Warsaw has made efforts to construct a new library building since 1920. It was then that the Director of Warsaw University Library submitted a request to the Senate for constructing a new structure needed for constantly increasing collections. The contemporary library building, which had existed hitherto, functioned in one of the biggest European universities. It was too small to house the whole collection as early as 1920 and yet the quantity of the collection has been rising all the time for the nearly 80 years. To be able to house the collection, auxiliary buildings, halls and basements were being destined. Some often priceless rarities and prints were kept in very bad conditions and could not be made available through lack of display possibilities. Access to the plenty of items was very difficult.